A High-Power Pulse Generator Based on Pulse Forming Network and Linear Transformer. (28th January 2021) - Li, Mingjia; Kang, Qiang; Tan, Jie; Luo, Min; Xiang, Fei
Abstract : With the development of high-power microwave technology, the output power of the pulse generator is required more and more higher. In this paper, it is realized by increasing the output power of the module while the output impedance of the module changes little. The module of the generator is based on pulse forming network (PFN) and linear transformer (LT). Four Blumlein PFNs with arc-type configuration and 24 Ω characteristic impedance were connected symmetrically to the primary coil of the LTD and driven by two identical laser triggered spark switches to ensure four Blumlein PFNs synchronizing operation. On this basis, a two-stage high-power pulse generator based on PFN-LT is developed. The following technical parameters of the generator were achieved on a 12 Ω high-power solid resistor: output voltage amplitude of ∼250 kV and output power of ∼5.2 GW at a repetition rate of 5 Hz.